Evidence of Halodule wrightii flower and seed production at its northern range extent in the western North Atlantic (USA) - Madison A. Lytle; Michael E. Wheeler (Aquatic Botany, 2025)

Applying microelectrodes to investigate aged ductile iron and copper coupon reactivity during free chlorine application - Jennifer E. Liggett; Beatriz C. Gonzalez; Darren A. Lytle; Jonathan G. Pressman; Dionysios D. Dionysiou; Woo Hyoung Lee; Stephen M. Harmon; David G. Wahman (Water Research, 2024)

Trends in flame retardant levels in upholstered furniture and children's consumer products after regulatory action in California - R. Gill; Q. Wang; S. Takaku-Pugh; E. Lytle; M. Wang; D.H. Bennett; J. Park; M. Petreas (Chemosphere, 2024)

Depth profiles of biological aerated contactors: Characterizing microbial activity treating reduced contaminants - Asher E. Keithley; Vicente Gomez-Alvarez; Daniel Williams; Hodon Ryu; Darren A. Lytle (Journal of Water Process Engineering, 2023)

Comprehensive characterization of aerobic groundwater biotreatment media - Asher E. Keithley; Hodon Ryu; Vicente Gomez-Alvarez; Stephen Harmon; Christina Bennett-Stamper; Daniel Williams; Darren A. Lytle (Water Research, 2023)

Climate change projections of continental-scale streamflow across the Mississippi River Basin - James W. Lewis; Sara E. Lytle; Ahmad A. Tavakoly (Theoretical and Applied Climatology, 2023)
A large body of scientific research has demonstrated a changing climate, which affects river flow regimes and extreme flood frequencies and magnitudes. The magnitude and frequency of extreme events are of critical importance in the evaluation of river systems to inform flood risk reduction under current and future conditions. The global climate projections from the Coupled Model Intercomparison Project, Phase 5 (CMIP5) datasets were used by the Variable Infiltration Capacity (VIC) land surface model to produce a runoff dataset, implementing a Bias-Correction Spatial Disaggregation (BCSD) approach. The resulting runoff was then used as input to the Routing Application for Parallel computatIon of Discharge (RAPID) river routing model to simulate daily flows within all 1.2 million Mississippi River Basin river reaches for years 1950 through 2099. This research effort analyzed the performance of the models for the historical time period, comparing with the observations at 64 gage locations for 16 different climate models. A recurrence interval analysis was performed to determine the 2-, 5-, 10-, 50-, 100-, 500-, and 1000-year events within both the historical and projected time periods, highlighting the relative changes predicted into the future. Anticipated seasonal changes are demonstrated by comparing monthly average streamflows for three different time periods (1951–2005, 2006–2049, and 2050–2099). Results indicate that the hydrologic conditions of the Lower Mississippi River are not stationary. Based on all 16 models considered in this study, the median of the model projections shows an 8% increase in the 100-year return period discharge at Vicksburg, Mississippi, into the future time period, although the full range of 16 models varies widely from − 11 to + 85% change in the 100-year discharge in the future.

Traits-based approaches support the conservation relevance of landscape genetics - Meryl C. Mims; Emily E. Hartfield Kirk; David A. Lytle; Julian D. Olden (Conservation Genetics, 2018)

High mortality and enhanced recovery: modelling the countervailing effects of disturbance on population dynamics - Laura E. McMullen; Patrick De Leenheer; Jonathan D. Tonkin; David A. Lytle (Ecology Letters, 2017)
Disturbances cause high mortality in populations while simultaneously enhancing population growth by improving habitats. These countervailing effects make it difficult to predict population dynamics following disturbance events. To address this challenge, we derived a novel form of the logistic growth equation that permits time‐varying carrying capacity and growth rate. We combined this equation with concepts drawn from disturbance ecology to create a general model for population dynamics in disturbance‐prone systems. A river flooding example using three insect species (a fast life‐cycle mayfly, a slow life‐cycle dragonfly and an ostracod) found optimal tradeoffs between disturbance frequency vs. magnitude and a close fit to empirical data in 62% of cases. A savanna fire analysis identified fire frequencies of 3–4 years that maximised population size of a perennial grass. The model shows promise for predicting population dynamics after multiple disturbance events and for management of river flows and fire regimes.

Linking multidimensional functional diversity to quantitative methods: a graphical hypothesis‐evaluation framework - Kate S. Boersma; Laura E. Dee; Steve J. Miller; Michael T. Bogan; David A. Lytle; Alix I. Gitelman (Ecology, 2016)
Functional trait analysis is an appealing approach to study differences among biological communities because traits determine species' responses to the environment and their impacts on ecosystem functioning. Despite a rapidly expanding quantitative literature, it remains challenging to conceptualize concurrent changes in multiple trait dimensions (“trait space”) and select quantitative functional diversity methods to test hypotheses prior to analysis. To address this need, we present a widely applicable framework for visualizing ecological phenomena in trait space to guide the selection, application, and interpretation of quantitative functional diversity methods. We describe five hypotheses that represent general patterns of responses to disturbance in functional community ecology and then apply a formal decision process to determine appropriate quantitative methods to test ecological hypotheses. As a part of this process, we devise a new statistical approach to test for functional turnover among communities. Our combination of hypotheses and metrics can be applied broadly to address ecological questions across a range of systems and study designs. We illustrate the framework with a case study of disturbance in freshwater communities. This hypothesis‐driven approach will increase the rigor and transparency of applied functional trait studies.

Ecological strategies predict associations between aquatic and genetic connectivity for dryland amphibians - Meryl C. Mims; Ivan C. Phillipsen; David A. Lytle; Emily E. Hartfield Kirk; Julian D. Olden (Ecology, 2015)
The study of how population genetic structure is shaped by attributes of the environment is a central scientific pursuit in ecology and conservation. But limited resources may prohibit landscape genetics studies for many threatened species, particularly given the pace of current environmental change. Understanding the extent to which species' ecological strategies—their life histories, biology, and behavior—predict patterns and drivers of population connectivity is a critical step in evaluating the potential of multi‐taxa inference in landscape genetics. We present results of a landscape genetic study of three dryland amphibians: the canyon treefrog ( Hyla arenicolor ), red‐spotted toad ( Anaxyrus punctatus ), and Mexican spadefoot ( Spea multiplicata ). These species characterize a range of ecological strategies, driven primarily by different water dependencies, enabling amphibian survival in arid and semiarid environments. We examined a suite of hypothesized relationships between genetic connectivity and landscape connectivity across species. We found a positive relationship between population differentiation and water dependency, e.g., longer larval development periods and site fidelity for reliable water sources. We also found that aquatic connectivity is important for all species, particularly when considered with topography (slope). The effect of spatial scale varied by species, with canyon treefrogs and Mexican spadefoots characterized by relatively consistent results at different scales in contrast to the stark differences in results for red‐spotted toads at different scales. Using ecological information to predict relationships between genetic and landscape connectivity is a promising approach for multi‐taxa inference and may help inform conservation efforts where single‐species genetic studies are not possible.

17 novel polymorphic microsatellite markers for the giant water bug, Abedus herberti (Belostomatidae) - T. S. Daly-Engel; R. L. Smith; D. S. Finn; M. E. Knoderbane; I. C. Phillipsen; D. A. Lytle (Conservation Genetics Resources, 2012)